2014
DOI: 10.3329/jbas.v38i2.21346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quail genotypes on hatchability traits, body weight and egg production

Abstract: A study was conducted with four genotypes of quail, namely Japanese (J), White (W), Black (Bl) and Brown (Br) quail with the objective to know their hatchability traits, body weight and egg production performances. The parent males and females were maintained in cages for single pair mating through close breeding system for producing each generation. A total of 1866-day-old chicks comprising of 4 types of quail namely J, W, Br, and Bl were hatched in a batch. The egg weight were 10.35 ± 0.3, 11.60 ± 0.42, 10.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
4
3
1
1
Order By: Relevance
“…Those values were higher than the present findings. On the other hand, for white, black and brown Japanese quail genotypes, Islam et al (2014) reported chick weight to egg weight ratios of 62.7%, 62.9%, 58.2% and 46.4%, which are lower than in the present study. This trait was reported as 66.9% by Dere et al (2005); as 64.5%, 62.8% and 66.5% for light (8.91 g), medium (9.80 g) and heavy (10.76 g) egg weight groups, respectively, by Adeyanju et al (2014) and as 69.4% by Alasahan et al (2016).…”
Section: Resultscontrasting
confidence: 99%
“…Those values were higher than the present findings. On the other hand, for white, black and brown Japanese quail genotypes, Islam et al (2014) reported chick weight to egg weight ratios of 62.7%, 62.9%, 58.2% and 46.4%, which are lower than in the present study. This trait was reported as 66.9% by Dere et al (2005); as 64.5%, 62.8% and 66.5% for light (8.91 g), medium (9.80 g) and heavy (10.76 g) egg weight groups, respectively, by Adeyanju et al (2014) and as 69.4% by Alasahan et al (2016).…”
Section: Resultscontrasting
confidence: 99%
“…The LSG 28 genotype was the fastest for SLG, GRBW and GRSL as compared with other genotypes. Significant effect of genotype on BW in Japanese quail is also in agreement with previous reports (Islam et al 2014;Hussain et al 2016) and SL (Grunder et al 1983;Dikmen & Ipek 2006). Mohammad (2016).…”
Section: Performance Of the Traitssupporting
confidence: 92%
“…Japanese quail are used widely as a model in breeding, physiology, nutrition, pathology, reproduction and immunology research (Huss et al 2008). Recently, quail rearing for commercial egg and meat production has become popular because of rapid economic returns from commercial quail production (Islam et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Celle-ci est influencée par un mélange de facteurs génétiques et non génétiques (âge, sexe ratio, alimentation, etc). Islam et al (2014) 1-Poids de l'oeuf entier 1 0,23 ** 0,78 *** 0,63 *** 0,01 0,28 *** 0,46 *** 0,75 *** 0,86 *** 2-Poids de coquille 1 0,22 ** 0,34 *** -0,04 ns 0,17 * 0,06 ns 0,24 *** 0,1 ns 3-Poids du blanc 1 0,43 *** 0,04 ns 0,19 ** 0,22 ** 0,60 *** 0,67 *** 4-Poids du jaune 1 -0,07 ns 0,29 *** 0,57 *** 0,59 *** 0,50 *** 5-Hauteur du blanc 1 0,06 ns -0,21 ** -0,03 NS 0,03 ns 6-Hauteur du jaune 1 -0,10 0,23 ** 0,23 ** 7-Diamètre du jaune 1 0,47 *** 0,34 *** 8-Longueur de l'oeuf 1 0,39 *** 9-Largeur de l'oeuf 1…”
Section: Performances De Ponteunclassified